Outcome Trajectory Evaluation (OTE): An Approach to Tackle Research-for-Development’s Long-Causal-Chain Problem - Douthwaite, Boru; Proietti, Claudio; Polar, Vivian; Thiele, Graham (SAGE Publications, 2023)
This paper develops a novel approach called Outcome Trajectory Evaluation (OTE) in response to the long-causal-chain problem confronting the evaluation of research for development (R4D) projects. OTE strives to tackle four issues resulting from the common practice of evaluating R4D projects based on theory of change developed at the start. The approach was developed iteratively while conducting four evaluations of policy-related outcomes claimed by the CGIAR, a global R4D organization. The first step is to use a middle-range theory (MRT), based on “grand” social science theory, to help delineate and understand the trajectory that generated the set of outcomes being evaluated. The second step is to then identify project contribution to that trajectory. Other types of theory-driven evaluation are single step: they model how projects achieve outcomes without first considering the overarching causal mechanism—the outcome trajectory—from which the outcomes emerged. The use of an MRT allowed us to accrue learning from one evaluation to the next.